2022
DOI: 10.2147/ijn.s338349
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Avoiding Protein Corona Inhibition of Targeted Drug Delivery by Linking Recombinant Affibody Scaffold to Magnetosomes

Abstract: Purpose: Nanoparticles (NPs) decorated with functional ligands are promising candidates for cancer diagnosis and treatment. However, numerous studies have shown that chemically coupled targeting moieties on NPs lose their targeting capability in the biological milieu because they are shielded or covered by a "protein corona". Herein, we construct a functional magnetosome that recognizes and targets cancer cells even in the presence of protein corona. Methods: Magnetosomes (BMPs) were extracted from magnetotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In the case of carbohydrate-decorated amphiphilic nanoparticles, a protein crown is formed in the biological environment based mainly on human serum albumin, complement proteins, apolipoproteins, and proteins involved in the coagulation cascade. Although the presence of these protein crowns significantly reduced the cellular uptake of amphiphilic assemblies, they also significantly reduced the cytotoxic and hemolytic effects resulting from the contact of NPs with living cells [ 129 ]. The ability to control protein corona formation with ligand molecules has been used to regulate the intracellular activation of nanoenzymes through endosomal proteolysis of coronal proteins [ 130 ].…”
Section: The Effect Of Protein Corona On Antibacterial Targeted Deliv...mentioning
confidence: 99%
“…In the case of carbohydrate-decorated amphiphilic nanoparticles, a protein crown is formed in the biological environment based mainly on human serum albumin, complement proteins, apolipoproteins, and proteins involved in the coagulation cascade. Although the presence of these protein crowns significantly reduced the cellular uptake of amphiphilic assemblies, they also significantly reduced the cytotoxic and hemolytic effects resulting from the contact of NPs with living cells [ 129 ]. The ability to control protein corona formation with ligand molecules has been used to regulate the intracellular activation of nanoenzymes through endosomal proteolysis of coronal proteins [ 130 ].…”
Section: The Effect Of Protein Corona On Antibacterial Targeted Deliv...mentioning
confidence: 99%
“…Careful modulation of the protein corona through the tuning of intrinsic and extrinsic parameters may allow nanoparticles to be delivered optimally in tumor tissue [ 72 ]. A study [ 73 ] has shown that linking Z domain-based recombinant affibody (RA) scaffolds to magnetosomes (BMPs), which were then preadsorbed on anti-HER2 humanized mAb (TZ) and incubated with human plasma, resulted in the more effective targeting capability and drug delivery of nanoparticles in a simulated in vivo environment by incorporating the majority of TZ molecules into the nanoparticle–corona complex. It is also crucial to consider external factors, such as temperature, pH, and shear stress, for developing a more efficient protein corona [ 74 ].…”
Section: Importance Of Physicochemical Properties Of Nanoparticlesmentioning
confidence: 99%
“… [236] , [238] , [239] , [240] , [245] , [246] The resulting impact may be complementary or deleterious [247] , [248] , [249] and thus worth examining for appropriate interventions. We anticipate that existing nanoparticle dispersion and stabilization strategies that leverage a careful control of the biophysical properties of phase formations and have been previously demonstrated in other protein-nanoparticle formulations [250] , [251] , [252] , [253] will be useful in circumventing protein corona and colloidal stability challenges in ACE2-based nano-pharmaceuticals. All the same, clinical safety validations of these approaches would determine their approval into clinical use.…”
Section: Outlook and Conclusionmentioning
confidence: 99%